2013
DOI: 10.3354/meps10478
|View full text |Cite
|
Sign up to set email alerts
|

Diet- and tissue-specific incorporation of isotopes in the shark Scyliorhinus stellaris, a North Sea mesopredator

Abstract: 14Elucidating predator-prey relationships is an important part of understanding and assessing the 15 structure and function of ecosystems. Sharks are believed to play a significant role in marine 16 ecosystems, although their specific trophic ecology is largely unexplored. Stable isotopes of 17 nitrogen (δ 15 N) and carbon (δ 13 C) are a widely applied tool in food web studies but there is a 18 need to quantify stable isotope dynamics in animals, particularly sharks. In this study, diet-tissue 19 discriminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 55 publications
1
30
0
Order By: Relevance
“…Our findings from sequentially sampled individuals, however, suggest a longer time period is needed to detect such changes, and that stable isotope data from a tissue with faster turnover rates (e.g. plasma δ 15 N half-life =~33 days, liver δ 15 N half-life =~39 days, whole blood δ 15 N half-life =~62 days; Caut et al, 2013;Kim et al, 2012;MacNeil et al, 2006;Malpica-Cruz et al, 2012), and/or using modeling approaches to test a priori hypotheses (e.g. Araujo et al, 2007;Lee et al, 2012;Matich and Heithaus, 2014) is more appropriate for detecting short-term shifts in elasmobranch trophic interactions.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Our findings from sequentially sampled individuals, however, suggest a longer time period is needed to detect such changes, and that stable isotope data from a tissue with faster turnover rates (e.g. plasma δ 15 N half-life =~33 days, liver δ 15 N half-life =~39 days, whole blood δ 15 N half-life =~62 days; Caut et al, 2013;Kim et al, 2012;MacNeil et al, 2006;Malpica-Cruz et al, 2012), and/or using modeling approaches to test a priori hypotheses (e.g. Araujo et al, 2007;Lee et al, 2012;Matich and Heithaus, 2014) is more appropriate for detecting short-term shifts in elasmobranch trophic interactions.…”
Section: Discussionmentioning
confidence: 69%
“…Hussey et al, 2012;Kinney et al, 2011;McMeans et al, 2010), yet relatively slow turnover times (e.g. muscle N250 days, Kim et al, 2012;fin N500 days, MacNeil et al, 2006) and few lab studies quantifying turnover rates and discrimination rates (Caut et al, 2013;Hussey et al, 2010a;Kim et al, 2012;Logan and Lutcavage, 2010;MacNeil et al, 2006;Malpica-Cruz et al, 2012) hinders our ability to interpret stable isotopes of elasmobranchs, especially among juveniles in which "maternal meddling" can greatly affect δ 13 C and δ 15 N values (Olin et al, 2011). Indeed, in placentatrophic sharks, embryos tend to have enriched isotopic values relative to their mothers, which persists into at least their first few months after birth, and may indicate that sharks are reliant on maternal energy reserves at the time of capture, despite feeding independently for weeks or even months prior to capture (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…A scaled discrimination factor framework, where higher dietary δ 15 N values result in lower trophic discrimination factors (Caut et al, 2013;Hussey et al, 2014;Olin et al, 2013), suggests that the deep-sea sharks sampled in this study span approximately two trophic levels. Experimental studies done on a limited number of elasmobranch species revealed δ 15 N discrimination factors ranging from 2.3‰ to 3.7‰ using lipid and urea extracted samples Kim et al, 2012aKim et al, , 2012b) and 1.1-1.8‰ using bulk muscle tissue Kim et al, 2012a;MalpicaCruz et al, 2012), but none of these experiments were conducted on deep-sea taxa.…”
Section: Ecological Dynamicsmentioning
confidence: 97%
“…The SEA c was used to calculate the degree of isotopic niche overlap, with associated 95% confidence intervals, representing a quantitative measure of dietary similarity between size classes. Ranges represent the range in δ To compare inter-and intra-specific resource use of the size classes of the 3 elasmobranchs, SEA c was calculated using their δ 13 C and δ 15 N data adjusted with the diet-tissue discrimination factors developed for elasmobranch fin tissues (Caut et al 2013; 1.06 ‰ Δ 13 C and 0.49 ‰ for Δ 15 N). The adjusted SEA c ellipses were graphed over the mean (± SD) stable isotope data of the representative consumer species pooled by 4 functional groups (i.e.…”
mentioning
confidence: 99%